Arthroscopic Posterior Glenoid Augmentation With Distal Tibial Allograft - Robert S. Dean MD; Eric J. Dennis MD; LeeAnne F. Torres MD; Danielle E. Rider BA; Nicholas A. Trasolini MD; Max D. Gehrman MD; Brian R. Waterman MD (SAGE Publishing, 2022)
Background: Posterior glenohumeral instability is much less common than anterior instability, and there is a paucity of studies looking at glenoid bone loss as it relates to posterior instability. However, while the data are not as robust, posterior glenoid bone loss can lead to recurrent instability and failed soft tissue procedures. Arthroscopic posterior glenoid augmentation with distal tibial allograft (DTA) is a minimally invasive option to restore stability and preserve function. Indications: The primary indication for posterior glenoid augmentation is posterior instability with >20% to 25% posterior glenoid bone loss or recurrent posterior instability after prior stabilization procedure. In this case, the patient is a 21-year-old man with recurrent instability after 2 prior soft tissue stabilization procedures. Technique Description: The patient was positioned in lateral decubitus, and portals were established. Arthroscopic evaluation was performed to assess the labrum, biceps, rotator cuff, glenoid, and humeral head. Glenoid mobilization was performed, and an incision was made for introduction of the bone block. The glenoid was prepared, and a trial was used to guide preparation of the graft, which was harvested from the articular cartilage of the distal tibia. The graft was irrigated and bathed in platelet-rich plasma (PRP) and then introduced and positioned for maximal coverage of the defect. Screw fixation was performed with two 3.75-mm screws. The posterior capsule was reapproximated, and a layered closure was performed. Results: Previous studies have reported significant improvements in patient-reported outcomes, high rates of healing, and no cases of recurrent instability after DTA for anterior glenoid bone loss. Additional studies have reported few patients with recurrent instability and no instances of partial or non-union. Significant loss of range of motion has not been reported in the most recent case series. One previous study reported significantly improved patient-reported outcomes and near-complete osseous reabsorption with DTA after failed Latarjet procedure. Discussion/Conclusion: Arthroscopic posterior glenoid augmentation with DTA is a viable treatment option for patients with shoulder pain and instability with >20% to 25% posterior glenoid bone loss and/or following prior stabilization procedures.